Field-Assisted and Thermionic Contributions to Conductance in SnO2 Thick-Films. (9th August 2009) - Malagù, C.; Carotta, M. C.; Martinelli, G.; Ponce, M. A.; Castro, M. S.; Aldao, C. M.
Abstract : A deep analysis of conductance in nanostructuredSnO 2 thick films has been performed. A model for field-assisted thermionic barrier crossing is being proposed to explain the film conductivity. The model has been applied to explain the behavior of resistance in vacuum of two sets of nanostructured thick-films with grains having two well-distinct characteristic radii (R = 25  nm andR = 125  nm). In the first case the grain radius is shorter than the depletion region width, a limit at which overlapping of barriers takes place, and in the second case it is longer. The behavior of resistance in the presence of dry air has been explained through the mechanism of barrier modulation through gas chemisorption.